Morphological Study of Word Formation on The Indonesian G20 Website - Haryati, Haryati; Maisari, Linda; Rahayu, Nike (Universitas Cokroaminoto Palopo, 2024)
This research focused on the Morphological Study of Word Formation on the Indonesian G20 Website. This research’s objectives were to identify and classify the word-formation types, processes, and meanings found in the selected articles on the Indonesian G20 Website. The writers used a descriptive-qualitative approach to analyze the data textually. The writers identified 98 words that indicate the word formation process. Moreover, through the 10 existing categories of the word formation process analyzed, 5 were identified. These categories included the borrowing type, which consisted of 21 words; the compounding type, which consisted of 12 words; the acronym type, which consisted of 14 words; the derivational type, which consisted of 48 words; and the multiple processes type, which consisted of 3 words. Nevertheless, the words resulting from coinage, blending, clipping, backformation, and conversion were not discovered. Furthermore, word formation can be generated through some processes, including borrowing from various languages, adding affixes, combining with other root words, and removing or shortening the word. Overall, the objective of each process of word formation is to create a new term that conveys meanings and grammatical categories that differ from the original word.